Heart rate variability and meditation: a meta-analysis. (19th May 2022) - Bin Waleed, K; Lakhani, I; Gong, M; Liu, T; Roever, L; Christien Li, KH; Rajan, R; Qasim Ibrahimi, M; Xia, Y; Tse, G; Chang, D; Lee, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Meditation can induce changes in autonomic balance, which can benefit cardiovascular health. The present meta-analysis evaluated changes in heart rate variability (HRV) in meditators. Methods: PubMed and Embase were searched for primary prospective studies using the search terms 'heart rate variability' and 'meditation' until January 18th, 2019. The statistical significance of the difference between subgroups is evaluated by the standardized mean difference (SMD), 95% confidence interval (CI), and P-value. I2 value was used to assess the statistical heterogeneity between the included studies. Results: Twenty-one studies involving 538 meditators (experienced= 209, beginners= 329) and 334 controls (mean age= 40.61, 35% male) were included. Regarding time-domain indices, no statistically significant differences were observed when assessing HRV between i) meditators versus controls (SMD= -0.17; 95% CI: [-0.50, 0.17]; p= 0.30; I2= 0%), ii) pre- versus post-meditation (SMD= -0.41; 95% CI: [-1.10, 0.28]; p= 0.25; I2= 80%) or iii) at baseline versus during meditation (SMD= -0.40; 95% CI: [-0.94, 0.14]; p= 0.14; I2= 72%). Pertaining to frequency-domain indices, analysis of low frequency (LF), normalized low frequency (LFnu) and high frequency (HF) between i) meditators versus controls, ii) at baseline versus post-meditation and iii) at baseline versus during meditation yet again did not show any variations. Seven studies assessed normalized high frequency (HFnu) at baseline versus during meditation collectively demonstrated a significantly higher HFnu during meditation in beginners with notable heterogeneity (SMD= 1.29; 95% CI: [0.09, 2.49]; p= 0.04; I2= 95). Moreover, LF/HF was evaluated by seven studies at baseline versus during meditation. Both meta-analysis (SMD= 0.76; 95% CI: [-0.17, 1.69]; p= 0.11; I2= 94%) as well as subset analysis of experienced meditators (SMD= -0.46; 95% CI: [-0.88, -0.03]; p= 0.03; I2= 0%) revealed a significantly lower LF/HF at baseline. Conclusions: Short-term changes in HRV indices were observed during meditation, but there is limited evidence for significant long-term effects.